PEMANFAATAN APLIKASI KINEMASTER SEBAGAI PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA DI SDN 04 MUARO SUNGAI LOLO - Doni Nofrizal; Firman; Desyandri (STKIP Subang, 2024)
Thematic learning at SDN Muaro Sungai Lolo has decreased in terms of quality and in the learning process. After being studied, this happened because the learning process was less effective and the teachers were less than optimal in conveying information related to learning materials. Where we know that usually during face-to-face learning, students are more focused and more effective in the teaching and learning process with direction and delivery from the teacher directly. Compared to current online learning, the use of smartphones as a communication tool in online learning is considered ineffective and inefficient. Because as we know that there are many other non-educational applications on smartphones that can interfere with students' concentration and focus. This has a significant impact on students, teachers and parents. This is certainly closely related to the learning system and the use of inappropriate learning media. This study uses a descriptive research method, using comparative data analysis of student grades for the last three years. The conclusion obtained is that at the beginning of making the video, the teachers used the kinemaster application as a support in this case. After operating this Mathematics learning video media to students.